It's not a math lesson - we're learning to draw! Teachers' use of visual representations in instructing word problem solving in sixth grade of elementary school. - Anton Boonen; Helen Reed; Judith Schoonenboom; Jelle Jolles (EARLI, 2016)
Non-routine word problem solving is an essential feature of the mathematical development of elementary school students worldwide. Many students experience difficulties in solving these problems due to erroneous problem comprehension. These difficulties could be alleviated by instructing students how to use visual representations that clarify the problem structure and the relations between solution-relevant elements (so-called visual-schematic representations). Research shows that instructional effectiveness depends largely on teachers' mathematical knowledge for teaching. Teachers' knowledge of visual representations is therefore essential to instructing word problem comprehension in this way. As there is little to no literature investigating teachers' practices in this area, the goal of the present study is to examine teachers' use of visual representations to support non-routine word problem solving. Eight mainstream elementary school teachers implemented an innovative approach focused on the use of visual-schematic representations. After a short training, teachers were able to produce these representations during instruction. However, some teachers seemed unclear about what these representations comprise and what function they serve within the word problem solving context. Teachers seemed to base their use of  representations on personal preferences rather than on an optimal fit with the word problem characteristics. These aspects need to be addressed in teacher training and professional development programs. This study makes an unique contribution to research in the important and problematic area of word problem solving in regular classrooms. The results of this study are relevant for educational researcher, teachers, and teacher educators who deal with difficulties in instructing mathematical word problems.